PENGARUH NET PROFIT MARGIN, DEBT TO ASSET RATIO, DAN RECEIVABLE TURNOVER TERHADAP RETURN ON ASSET PADA PERUSAHAAN SUB SEKTOR PERDAGANGAN BESAR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2016-2019 - Chasanah, Fia Nur; Supeno, Saras; Budiyah, Feriani (Universitas Of Surakarta, 2022)
The results of the analysis and discussion that can be taken in this study are that partially Net Profit Margin and Receivable Turnover have a positive and significant effect on Return On Asset in large trading sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2016-2019. This is evidenced by the value of the coefficient of the Net Profit Margin variable which is positive and the significance value of 0.000 is smaller than the limit of the significance value of 0,05, and the value of tcount (9,029) is greater than the ttable value (1,67655), and the coefficient value. Receivable Turnover variable which is positive and the significance value of 0,000 is smaller than the limit of the significance value of 0,05, and the value of tcount (5,905) is greater than the value of ttable (1,67655). Meanwhile, the Debt To Asset Ratio has a positive coefficient value but does not have a significant effect on Return On Asset in large trading sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2019 period. This is evidenced by the value of the coefficient of the Debt To Asset Ratio variable which is positive and a significance value of 0,377 is greater than the limit of the significance value of 0,05, and the value of tcount (0,891) is smaller than the ttable value (1,67655). Simultaneously, Net Profit Margin, Debt To Asset Ratio, and Receivable Turnover have an effect on Return On Asset in large trading sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2019 period. This is evidenced by the significance coefficient value on the test results simultaneously (ANOVA). The significance value of 0,000 is smaller than the limit of the significance value of 0.05 and the value of Fcount (37,769) is greater than the value of Ftable (2,79).